Intersectoral collaboration in the COVID-19 response in Latin America and the Caribbean - Donald T. Simeon; Victor Cuba; Shelly-Ann Hunte; Kershelle Barker; Midori de Habich (BMC, 2024)
Abstract World Health Organization (WHO) / Pan American Health Organization (PAHO) encouraged the utilization of whole-of-society and whole-of-government strategic approaches to increase countries' resilience towards mitigating the impact of the COVID-19 pandemic. Strategies included the implementation of multi-sectoral, multi-partner and multi-stakeholder planning, coordination, consultation, and action. We reviewed the experiences of three Latin American and Caribbean countries, related to the implementation of collaborative strategies in tackling COVID-19, specifically the nature of the collaboration, the dynamics and the stakeholders involved. A systematic literature review identified relevant publications and content analysis was conducted to determine the collaborative strategies. Colombia, Costa Rica, and Trinidad and Tobago were selected as case studies since they were from different LAC subregions and because of the accessibility of relevant literature. In the three countries, the pandemic response was coordinated by a national executive committee, led by the Ministry of Health. Intersectoral collaboration was evident in each, with the key stakeholders being public sector agencies, the private/corporate sector, private/non-profit, academic institutions, and international agencies. It was used primarily to facilitate data-driven, evidenced-informed decision-making and guidelines; to expand clinical care capacity and strengthen the national medical response; and to provide support for the most vulnerable populations. While the institutionalization of intersectoral collaboration can be recommended for the health sector beyond the pandemic, research is needed to evaluate the impact of specific collaborative strategies as well as barriers and facilitators.